Dynamic Contrast-Enhanced Computed Tomography–Derived Blood Volume and Blood Flow Correlate With Patient Outcome in Metastatic Renal Cell Carcinoma. Issue 2 (February 2017) - Mains, Jill Rachel; Donskov, Frede; Pedersen, Erik Morre; Madsen, Hans Henrik Torp; Rasmussen, Finn
Abstract : Objectives: The aim was to explore the potential for using dynamic contrast-enhanced computed tomography as a noninvasive functional imaging biomarker before and during the early treatment of metastatic renal cell carcinoma (mRCC). Materials and Methods: Dynamic contrast-enhanced computed tomography scans were performed at baseline and after 5 and 10 weeks' treatment in 69 prospectively included mRCC patients receiving treatment with interferon alpha and interleukin 2 (n = 26); interferon alpha, interleukin 2, and bevacizumab (n = 24); sunitinib (n = 7); pazopanib (n = 5); or temsirolimus (n = 7). Using a prototype software program (Advanced Perfusion and Permeability Application, Philips Healthcare, Best, the Netherlands), blood volume (BV), blood flow (BF), and permeability surface area product (PS) were calculated for each tumor at baseline, week 5, and week 10. These parameters as well as relative changes between baseline and weeks 5 and 10 were tested for associations with progression-free survival (PFS) and overall survival (OS) using Kaplan-Meier curves and log-rank tests. Results: Using the 25th percentile as the cutoff, baseline BV for all patients independent of subsequent treatment was statistically significantly associated with PFS (10.8 vs 5.3 months, P = 0.007) and OS (35.2 vs 13.3 months, P = 0.001), and baseline BF was significantly associated with OS (31.7 vs 14.6 months, P = 0.024) with high values for both parameters being associated with significantly longer PFS and OS. Baseline PS was not associated with PFS or OS. In patients treated with angiogenesis inhibitors (bevacizumab, sunitinib, pazopanib, or temsirolimus), the relative change in BV from baseline to week 5 using 25th percentile as the cutoff was associated with PFS (5.6 vs 24.8 months, P = 0.001) and OS (19.1 months vs not reached, P = 0.008) and from baseline to week 10 with PFS (8.1 vs 16.4 months, P = 0.014) and OS (15.5 months vs not reached, P = 0.002). The relative change in BF from baseline to week 5 using medians as the cutoff was associated with PFS (5.5 vs 14.3 months, P = 0.018) and OS (14.6 vs 31.7 months, P = 0.027). The relative change in BF from baseline to week 10 using 25th percentile as the cutoff was associated with PFS (8.3 vs 46.9 months, P = 0.011) and OS (19.1 vs 53.0 months, P = 0.006). For both parameters, the largest reductions during early treatment were associated with increased PFS and OS. In patients receiving immunotherapy only (interferon alpha and interleukin 2), relative changes in PS between baseline and weeks 5 and 10 were significantly associated with PFS with larger increases associated with longer PFS. In patients receiving angiogenesis inhibitors, the relative changes in PS between baseline and week 10 were significantly associated with PFS and OS with larger reductions associated with favorable outcomes. Conclusions: In patients with mRCC treated with angiogenesis inhibitors, the largest reductions in BV and BF between baseline and weeks 5 and 10 were associated with favorable outcomes. At baseline, the lowest BV and BF were associated with the poorest outcomes regardless of the subsequent treatment. Early reductions in PS were associated with favorable outcomes for those treated with angiogenesis inhibitors and with poor outcomes for those treated with immunotherapies.